The Representation of Americanization Myths in the Internet Memes on the 9gag Comedy Website - Ryan Aditya Achadiat (Universitas Pendidikan Indonesia (UPI), 2013)
The use of Internet memes in the websites is believed to be a new media to disseminate important ideologies and cultural values which represent the current norms of people in today's life. Dealing with this issue, this study entitled “The Representation of Americanization Myths in the Internet Memes on the 9GAG Comedy Website” is aimed at investigating the Myths of Americanization of 9GAG Internet memes in the Hot Page of the website where the popular Internet memes are provided. The data consisted offive9GAG Internet memes which were taken from the 9GAG Hot Page. This study used a qualitative descriptive approach framed in a semiotic analysis, specifically Barthes’ (1991) orders of signification to examine the myths in each Internet meme. The myths of the Internet memes then were analyzed using the USA’s values and assumptions theory proposed by Althen and Bennett (2011). The findings reveal that there are eight myths of Americanization which are delivered globally through the Internet memes. Those are individualism, freedom, equality, materialism, and informality. The myths of Americanization are represented through the symbolic signs in the Internet memes which represent the United States of America.Keyword: Semiotic, Orders of Signification, Myth, Meme, and Internet Meme.